Remyelination in Multiple Sclerosis: the therapeutic potential of neural and mesenchymal stem/progenitor cells - Rivera, Francisco J.; Kraus, Jörg; Steffenhagen, Carolin; Kury, Patrick; Weidner, Norbert; Aigner, Ludwig (Current signal transduction therapy, 2011)
Multiple sclerosis (MS) is a demyelinating immune-mediated disease of the central nervous system (CNS). It is the most common cause of acquired disability in young adults and affects over 2 Mio people worldwide. Current treatments target primarily the immune system, reduce the relapse rate and the formation of inflammatory lesions in the CNS, however with only temporary and limited success. Unfortunately, self-repair mechanisms of the CNS have been largely neglected in the past. The identification of neural and oligodendroglial progenitors in the brain and spinal cord, however, evoked the hypothesis that remyelination might be achieved through the activation of endogenous progenitors leading ultimately to functional recovery of the patient. Indeed, spontaneous remyelination is a common feature in MS, at least in the early phases of the disease, however, its levels and its qualities are apparently insufficient for a sustained endogenous functional repair. Here, we review the current knowledge on remyelination mechanisms and describe recent developments on molecular as well as on neural and mesenchymal stem cell therapies for MS treatment.
Gesehen am 16.09.2022